The impact of climate factors on crime types in Sulaymaniyah Governorate - خدر, نصر عمر خدر; سعید, آ.م.د. پاکیزە عەزیز سعید (Sulaimani Journal for Humanities, 2025)
Climatic factors significantly impact various aspects of human activity, particularly individual stability and psychological balance. Understanding the role of these factors in the emergence and diversity of crime is essential to determining the extent and nature of their impact, as well as the specific ways in which various climatic factors contribute to fluctuations in crime rates and types. This research was conducted under the title "The Impact of Climate Types on Crime Types in Sulaymaniyah Governorate." The study focuses on Sulaymaniyah Governorate, which is geographically located between latitudes 34°55′11" north and 36°30′41" north, and longitudes 44°37′54" east and 46°20′56" east, covering an area of 14,047.97 square kilometers. Administratively, the governorate comprises 13 districts. The research is divided into three main sections. The first section provides a conceptual review of crime and the main theories that explain criminal behavior. The second section examines regional climate characteristics, the relationship between climatic elements and crime rates, and seasonal variation in crime types in Sulaymaniyah Governorate. The final section analyzes and interprets the collected data using descriptive, analytical, and comparative approaches. The results reveal a relationship between seasonal variations and crime rates and types. Climatic factors play a significant role in shaping criminal behavior, contributing to crime through their impact on human physiological stability.
Keywords: (Climate Change; Sulaimani Province; Crime; Social Disorganization; Cultural Conflict)